2011
DOI: 10.1007/s11655-011-0670-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inotodiol extracts from inonotus obliquus on proliferation cycle and apoptotic gene of human lung adenocarcinoma cell line A549

Abstract: Inotodiol can inhibit proliferation and induce the apoptosis of A549 cells, and its molecular mechanism may be associated with the up-regulating expression of p53 and bax proteins and down-regulating expression of Bcl-2 protein, which arrested A549 cells in S phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…An in vitro study in human colon cancer cells (HT‐29) further revealed that ethanolic extracts of I. obliquus reduced the levels of CDK2 and CDK4, increased the expression of p53, p21, and p27, and arrested the proliferation of the cancer cells at the G 1 phase (Lee, Kim, & Kim, ). Similarly, the exposure of human lung adenocarcinoma cell line (A549 cell line) to inotodiol extract from I. obliquus reduced the expression of Ki‐67 and arrested the proliferation of the cells at the S phase in a dose‐dependent manner (Zhong, Wang, & Sun, ). In addition, the exposure of human gastric BGC2823 cell line to 80 mg/L of I. obliquus extract enhanced caspase‐3 and Bax expression and reduced the expression of Bcl‐2 (Zhong, Sun, Gao, et al, ).…”
Section: Inhibitory Effect Of I Obliquus Extracts On Tumor Growth Anmentioning
confidence: 99%
“…An in vitro study in human colon cancer cells (HT‐29) further revealed that ethanolic extracts of I. obliquus reduced the levels of CDK2 and CDK4, increased the expression of p53, p21, and p27, and arrested the proliferation of the cancer cells at the G 1 phase (Lee, Kim, & Kim, ). Similarly, the exposure of human lung adenocarcinoma cell line (A549 cell line) to inotodiol extract from I. obliquus reduced the expression of Ki‐67 and arrested the proliferation of the cells at the S phase in a dose‐dependent manner (Zhong, Wang, & Sun, ). In addition, the exposure of human gastric BGC2823 cell line to 80 mg/L of I. obliquus extract enhanced caspase‐3 and Bax expression and reduced the expression of Bcl‐2 (Zhong, Sun, Gao, et al, ).…”
Section: Inhibitory Effect Of I Obliquus Extracts On Tumor Growth Anmentioning
confidence: 99%
“…Traditional medicines derived from medicinal mushrooms are increasingly being used to treat a wide variety of clinical conditions (Youn et al, 2009) and anticancer studies of active ingredients extracted from mushrooms have become a research hotspot in the recent years (Zhong et al, 2011). Indeed, approximately 700 species of medicinal mushrooms have been found to inhibit the growth of different kinds of cancers (Lemiezek et al, 2011).…”
Section: Mushroomsmentioning
confidence: 99%
“…In recent years, more than 20 different kinds of bioactive components have been found in I. obliquus, including triterpenoids, polyphenols, steroids, b-glucan, peptides, and polysaccharides, suggesting a high medicinal value and good prospects for market development (Hu et al, 2009;Song et al, 2013). Triterpenoids such as inotodiol, lanosterol, and trametenolic acid are considered the main antitumor ingredients being able to induce growth inhibition, cell cycle arrest, and apoptosis in different cancer cells; however, the exact molecular mechanisms by which these effects occur are still not well understood (Chung et al, 2010;Du et al, 2011;Nomura et al, 2008;Youn et al, 2009;Zhong et al, 2011). Polysaccharides from I. obliquus can indirectly be involved in anticancer processes mainly via stimulating the immune system (Lee et al, 2009;Song et al, 2013).…”
Section: Mushroomsmentioning
confidence: 99%
“…34 Recent literature has extensively documented antioxidant, antitumor, and hypoglycemic activity. [35][36][37][38][39] The agent is used in Japan for a variety of benign and malignant conditions. Sandbath treatment.…”
Section: 33mentioning
confidence: 99%